BAHAN AJAR PADA MATERI GARIS SINGGUNG LINGKARAN DENGAN PENDEKATAN SAINTIFIK UNTUK SISWA SMP - Sowanto Sowanto (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
This research is motivated by the lack of teaching materials on tangent topic to the circle that is able to facilitate junior high school students through a scientific approach. This research produced teaching materials so-called students' worksheets that can facilitate students. The research used the design research which includes: (1) preliminary design, in this phase the researchers conducted a theory study which followed up by making a Hypothetical Learning Trajectory (HLT); (2) experiment, in this phase, the existing design is tested to the students to investigate the learning process that related to the process of developing students' thinking in situations and learning atmosphere that formed from HLT; (3) retrospective analysis, in this phase, the researchers compare the HLT with the actual student learning process. The results show that the teaching materials that have been developed by considering obstacle learning and preliminary studies are able to facilitate students as a source of support for learning activities.